(untitled) (Research, Society and Development, 2023)
Gestational Diabetes Mellitus (GDM) is the most common metabolic disorder during pregnancy and, without adequate glycemic control, can cause serious consequences for the mother, fetus and newborn. Therefore, the present study aimed to evaluate the clinical-epidemiological profile of patients with gestational diabetes mellitus treated at the Specialized Women’s Health Unit, through descriptive, cross-sectional research with a quantitative approach. For this, data collection was carried out through the medical records of pregnant women treated at the high-risk prenatal service of the Specialized Women’s Health Unit from January to December 2022. In this way, a GDM prevalence of 23.9% was obtained. Among the pregnant women affected, there was a predominance of women over 35 years of age, of mixed race, with complete secondary education and who lived in a stable relationship or were married. Regarding antecedents, a higher incidence of GDM was noted in multiparous women and women without previous abortions, in addition, 28.1% had a family history of diabetes mellitus. In relation to physical activity, only 13.2% reported doing it during pregnancy. Regarding GDM, 50.4% of patients were diagnosed in the second trimester of pregnancy, in addition, only 13.2% of women required the use of insulin. Furthermore, 28.9% consulted until the postpartum period. Regarding comorbidities, 54.5% were obese and 19.8% reported chronic hypertension. Therefore, the importance of measures aimed at preventing this pathology is noted, with emphasis on changes in lifestyle.